Life-Threatening Influenza, Hemophagocytic Lymphohistiocytosis and Probable Vaccine-Strain Varicella in a Novel Case of Homozygous STAT2 Deficiency - Bishara J. Freij (Frontiers in Immunology, 2021)
STAT2 is a transcription factor that plays an essential role in antiviral immunity by mediating the activity of type I and III interferons (IFN-I and IFN-III). It also has a recently established function in the negative regulation of IFN-I signaling. Homozygous STAT2 deficiency is an ultra-rare inborn error of immunity which provides unique insight into the pathologic consequence of STAT2 dysfunction. We report here a novel genetic cause of homozygous STAT2 deficiency with several notable clinical features. The proband presented aged 12 months with hemophagocytic lymphohistiocytosis (HLH) closely followed by clinical varicella, both occurring within three weeks of measles, mumps, and rubella (MMR) and varicella vaccinations. There was a history of life-threatening influenza A virus (IAV) disease 2 months previously. Genetic investigation uncovered homozygosity for a novel nonsense variant in STAT2 (c. 1999C>T, p. Arg667Ter) that abrogated STAT2 protein expression. Compatible with STAT2 deficiency, dermal fibroblasts from the child demonstrated a defect of interferon-stimulated gene expression and a failure to mount an antiviral state in response to treatment with IFN-I, a phenotype that was rescued by lentiviral complementation by wild type STAT2. This case significantly expands the phenotypic spectrum of STAT2 deficiency. The occurrence of life-threatening influenza, which has not previously been reported in this condition, adds STAT2 to the list of monogenetic causes of this phenotype and underscores the critical importance of IFN-I and IFN-III to influenza immunity. The development of probable vaccine-strain varicella is also a novel occurrence in STAT2 deficiency, implying a role for IFN-I/III immunity in control of attenuated varicella zoster virus in vivo and reinforcing the susceptibility to pathologic effects of live-attenuated viral vaccines in disorders of IFN-I immunity. Finally, the occurrence of HLH in this case reinforces emerging links to hyperinflammation in patients with STAT2 deficiency and other related defects of IFN-I signaling—highlighting an important avenue for further scientific enquiry.